Microbial rescue effects: How microbiomes can save hosts from extinction. (21st January 2020) - Mueller, Emmi A.; Wisnoski, Nathan I.; Peralta, Ariane L.; Lennon, Jay T.
Abstract: Rescue effects arise when ecological and evolutionary processes restore positive intrinsic growth rates in populations that are at risk of going extinct. Rescue effects have traditionally focused on the roles of immigration, phenotypic plasticity, gene flow, and adaptation. However, species interactions are also critical for understanding how populations respond to environmental change. In particular, the fitness of plant and animal hosts is strongly influenced by symbiotic associations with the bacteria, archaea, microeukaryotes and viruses that collectively make up a host's microbiome. While some are pathogenic, many microorganisms confer nutritional, immunological, and developmental benefits that can protect hosts against the effects of rapid environmental change. Microbial rescue occurs when changes in microbiome abundance, composition, or activity influence host physiology or behaviour in ways that improve host fitness. If these microbial attributes and their beneficial effects are transmitted through a population, it may stabilize growth rates and reduce the probability of extinction. In addition to providing a framework to guide theoretical and empirical efforts in host‐microbiome research, the principles of microbial rescue may also be useful for adaptively managing at‐risk species. We discuss the risks and rewards of incorporating microbial rescue into conservation strategies such as probiotics, assisted migration, and captive breeding. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.